Presidential Address: Demand‐Side Constraints in Development. The Role of Market Size, Trade, and (In)Equality - Goldberg, Pinelopi Koujianou; Reed, Tristan (Econometrica, 2023)
What is the pathway to development in a world marked by rising economic nationalism and less international integration? This paper answers this question within a framework that emphasizes the role of demand‐side constraints on national development, which is identified with sustained poverty reduction. In this framework, development is linked to the adoption of an increasing returns to scale technology by imperfectly competitive firms that need to pay the fixed setup cost of switching to that technology. Sustained poverty reduction is measured as a continuous decline in the share of the population living below $1.90/day purchasing power parity in 2011 U.S. dollars over a five‐year period. This outcome is affected in a statistically significant and economically meaningful way by domestic market size, which is measured as a function of the income distribution, and international market size, which is measured as a function of legally‐binding provisions to international trade agreements, including the General Agreement on Tariffs and Trade, the World Trade Organization, and 279 preferential trade agreements. Counterfactual estimates suggest that, in the absence of international integration, the average resident of a low‐ or lower‐middle‐income country does not live in a market large enough to experience sustained poverty reduction. Domestic redistribution targeted towards generating a larger middle class can partially compensate for the lack of an international market.